PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DI MTs AL URWATUL WUTSQO JOMBANG - Budiyono, Ahmad (ILJ: Islamic Learning Journal, 2024)
The Head of Madrasah has an important role in developing Educators and Education Personnel in the School, one of which is with Training and Development. Training and development is one of the functions of Human Resource Management. The implementation of training and development at MTs Al Urwatul Wutsqo Jombang has been carried out even though it has not been effective but the activities at school have been running according to the rules that have been set. Then the formulation of the problem is to find out how the implementation of training and development of human resources at MTs Al Urwatul Wutsqo Jombang. The research method uses descriptive qualitative. The data sources used are primary data and secondary data. The data collection methods used are interview, observation and documentation methods. Based on the results of this study, the implementation of training and human resource development in Al Urwatul Wutsqo Jombang has been well implemented, which is evidenced by the training process, namely by: determining the training needs to be carried out, training design, training implementation, training assessment. As for the development, it is proven by the existence of: career planning, career development, organizational development and performance appraisal management.